Effects of high fat diet on kidney lipid content and the Na,K-ATPase activity (Brazilian Journal of Pharmaceutical Sciences, 2018)
It is widely known that high fat diet (HFD) can contribute to the advent of health problems. Recent studies have indicated that obesity imposes a hemodynamic overload to the kidneys. In order to further investigate such injuries, two groups of six Swiss mice each were fed with a controlled AIN93G diet or a high fat (AIN93G modified) diet for eight weeks. Blood samples were collected to determine the hormonal, lipid profile, glucose, urea, and creatinine levels. Histopathological and immunohistochemical analysis were carried out to analysis the kidney damage. Fractions of renal membranes were prepared to assess the Na,K-ATPase activity, lipid peroxidation, total cholesterol, and phospholipid content. The results indicated that the blood lipid profile, urea and creatinine was not altered by the HFD. On the other hand, it was observed in HFD diet mice elevated glucose blood levels along with an augment on insulin and a decrease on corticosterone release. HFD provoked a reduction in the diameter of the convoluted tubules and cell volume in Bowman’s capsule and an increased number of positive cells with Na,K-ATPase, but reduced the Na,K-ATPase activity and the cholesterol content in the kidney cell membrane but favored the lipid peroxidation.